Effect of Using ICT on Learning Mathematics in Selected Secondary Schools in Makurdi Metropolis - Musa, D. C.; Garba, Adamu (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2019)
This study reviewed conceptual, theoretical and empirical literatu re on problem affecting the effective use of information and communication technology in teaching and learning of mathematics in secondary schools. Secondary source of information based on prior studies on the subject are examined in terms of methodology, research findings and recommendations. Descriptive research methodology was used to analyze the content of the theoretical, conceptual and empirical literature for this study. The study was anchored on Radical Constructivism Theory and Social Constructivism Theory. According to the study, technology is developed to solve problems associated with human need in more productive ways. If there is no problem to solve, the technology may not be developed and/or not adopted. Applying this principle to educational technology would mean that educational institution should create and adopt technologies that address educational problems, of which there are many. Majority of the findings from most of the empirical review indicates a positive relationship between teaching and learning of Mathematics and the use of information and communication technology in secondary schools. Those that indicates a negative relationship states that lack of knowledge of the teachers, low level of training and retraining of resource person, lack of relevant equipment, poor infrastructures, such as computers, network and power especially in the rural areas are some of the factors that makes the use of information and communication technology inhibit the teaching and learning of mathematics in secondary schools. It was concluded that the use of ICT in teaching and learning mathematics can make the teaching process more efficient as well as enhance the students’ capabilities in understanding basic concepts. It was recommended among others that the government, academic institutions and different stakeholders such as curriculum planners, policy makers, experts, teachers, students and parents to be serious and aware of these issues and their consequence.